2015
DOI: 10.1136/gutjnl-2015-310602
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the European achalasia trial: a multicentre randomised controlled trial comparing pneumatic dilation versus laparoscopic Heller myotomy

Abstract: Netherlands trial register (NTR37) and Current Controlled Trials registry (ISRCTN56304564).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
253
4
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(285 citation statements)
references
References 25 publications
12
253
4
16
Order By: Relevance
“…Because of the propensity of this procedure to cause reflux, LHM is usually combined with a partial fundoplication. An extensive literature has compared LHM with pneumatic dilation 51 , culminating in a multi center European randomized controlled trial comparing the two for the treatment of achalasia, which concluded that both approaches were ~90% effective with no statistically significant difference in therapeutic success between them 56,57 . However, that trial (and all preceding trials) did not consider achalasia subtypes in their design or in their assessment of treatment efficacy.…”
Section: Lhm and Pneumatic Dilationmentioning
confidence: 99%
“…Because of the propensity of this procedure to cause reflux, LHM is usually combined with a partial fundoplication. An extensive literature has compared LHM with pneumatic dilation 51 , culminating in a multi center European randomized controlled trial comparing the two for the treatment of achalasia, which concluded that both approaches were ~90% effective with no statistically significant difference in therapeutic success between them 56,57 . However, that trial (and all preceding trials) did not consider achalasia subtypes in their design or in their assessment of treatment efficacy.…”
Section: Lhm and Pneumatic Dilationmentioning
confidence: 99%
“…In the studies by Boeckxstaens et al [20], Moonen et al [19], Wang et al [21], Tabola et al [22], the authors used the Eckardt score to assess the success rate, while Tabola et al applied the symptom improvement rate by reduction of the Eckardt score and by evaluating the frequency of reintervention. In 4 other studies, symptom evaluation was based on various dysphagia scores.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative symptom assessment was similar in two studies, Moonen et al [19] and Boeckxstaens et al [20]: the primary outcome of these studies was therapeutic success (a reduction in the Eckardt score to ≤3). Two other studies [21,22] also used Eckardt score to evaluate the therapeutic success.…”
Section: Success Ratementioning
confidence: 98%
See 1 more Smart Citation
“…However, 25% of patients treated with pneumatic dilatation required re-dilatations. In subgroup and risk factor analysis, age less than 40 years, pre-existing daily chest pain, a pre-treatment esophageal width of less than 4 cm and type III achalasia were identified as risk factors for treatment failure or requiring re-dilatation in the pneumatic dilatation group (6).…”
Section: Introductionmentioning
confidence: 99%